Al-Ghazali on Taqlid, Ijtihad, and Forming Beliefs - Alhayyani, Mesfer (Conatus - Journal of Philosophy, 2024)
Medieval philosophy has often been stereotypically characterized as rigidly reliant on authority and lacking originality. However, the present research challenges this perception by unveiling the lively debates among medieval philosophers in the Islamic World regarding the autonomy of thought for both esteemed scholars and everyday individuals. Rather than passively accepting authoritative doctrines, these philosophers contemplated the extent to which independent reflection should play a role. Surprisingly, their reflections resonate in the contemporary world as we grapple with parallel questions about the balance between authority and individual inquiry in our society. The first part of the paper introduces a timeless challenge faced by medieval Islamic philosophers: the formation of beliefs. This predicament persists today – how much should we rely on authority without critical examination, and when should we subject our beliefs to scrutiny? The paper introduces an Islamic classical tradition followed by Muslim jurists, theologians, and philosophers: the nuanced distinction between Taqlid (following authority) and Ijtihad (independent reasoning) to address this. The perspective of Al-Ghazali, a prominent representative of this tradition, is thoroughly examined, highlighting its contributions and challenges. In its methodological approach, this paper rigorously analyzes primary and secondary sources relevant to Al-Ghazali’s views in Arabic and English. This comprehensive analysis aims to contribute to a more nuanced understanding of the intricate interplay between authority and independent reasoning in the context of medieval Islamic philosophy.